2019
DOI: 10.1097/bot.0000000000001578
|View full text |Cite
|
Sign up to set email alerts
|

Does Operative Intervention Provide Early Pain Relief for Patients With Unilateral Sacral Fractures and Minimal or No Displacement?

Abstract: Objectives: To compare pain after operative versus nonoperative pelvic ring injuries with unilateral sacral fractures. Design: Prospective, multicenter, observational. Setting: Sixteen trauma centers. Patients/Participants: Skeletally mature patients with pelvic ring injury and minimally displaced unilateral zone 1 or 2 sacral fractures and without anteroposterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
0
33
0
2
Order By: Relevance
“…Tornetta et al have already shown that stabilisation of sacral fractures improves pain. 22 Though it is still not clear whether or not this is to a clinically relevant level. The second indication of instability is where consensus has yet to be reached.…”
Section: Discussionmentioning
confidence: 99%
“…Tornetta et al have already shown that stabilisation of sacral fractures improves pain. 22 Though it is still not clear whether or not this is to a clinically relevant level. The second indication of instability is where consensus has yet to be reached.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the treatment, the examination under anesthesia (EUA) for lateral compression fractures was introduced, but their interpretation shows a relevant disagreement 23 . Furthermore, the deduced treatment and the consensus might change upon newer data 24 – 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Geriatrische Patienten mĂŒssen somit nicht nur initial bildmorphologisch beurteilt und evaluiert werden, sondern auch im kurz-und mittelfristigen Verlauf anhand der MobilisationsfĂ€higkeit und der möglichen radiologischen Frakturprogression. Von jungen Patienten ist bekannt, dass Patienten mit einer Denis I und/oder nicht-dislozierten Fraktur hĂ€ufiger konservativ behandelt werden, wohingegen Patienten mit einer Denis II und/oder dislozierten Fraktur eher operativ behandelt werden [15]. Zwar zeigte die operative Behandlung bei jungen Patienten auch statistisch eine verringerte SchmerzintensitĂ€t, jedoch bleibt fraglich, ob diese klinisch relevant ist [15].…”
Section: Therapieunclassified
“…Von jungen Patienten ist bekannt, dass Patienten mit einer Denis I und/oder nicht-dislozierten Fraktur hĂ€ufiger konservativ behandelt werden, wohingegen Patienten mit einer Denis II und/oder dislozierten Fraktur eher operativ behandelt werden [15]. Zwar zeigte die operative Behandlung bei jungen Patienten auch statistisch eine verringerte SchmerzintensitĂ€t, jedoch bleibt fraglich, ob diese klinisch relevant ist [15].…”
Section: Therapieunclassified